Pencegahan Stunting melalui Komunikasi Antar Pribadi di Kelurahan Mata Air, Kecamatan Padang Selatan, Kota Padang - Wira Iqbal; Dini Nur Annisa; Dyki Gymnasdian; Hana Salsabila Putri; Husnaa Haniifah Wizi; Muhammad Fakhraihansyah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2023)
Stunting or stunted children is a disorder of growth and development due to chronic malnutrition and repeated infections, characterized by their height being below the standards of the Ministry of Health. The stunting rate in Mata Air Village, South Padang District, is also reasonably high. Based on data obtained in October 2022, the number of stunting cases in Mata Air Village is 64 children. It was due to the lack of knowledge of pregnant women about stunting and the low economy of the community in the village. This activity aimed to practical the Interpersonal Communication approach in increasing the knowledge of pregnant women about stunting. The methods used were group discussion and Emotional Demonstration (Emo-Demo) with the application of Interpersonal Communication. The results showed an increase in knowledge from pregnant women. It proved that the Interpersonal Communication approach was quite effective in increasing the knowledge of pregnant women about stunting. The activity received a positive response from the people of Mata Air Village so that it could be carried out sustainably. Therefore, the Interpersonal Communication approach can increase mothers' knowledge about stunting and help prevent stunting in Mata Air Village.